Investigation on Influence of Ultrasonic Impact Treatment (UIT) on Fatigue Life for Aluminium Alloy 2017-T4 - Alalkawi, Hussain J. M.; Alhamdany, Aseel A.; Abdul Hassan, Marib R. (Al-Nahrain Journal for Engineering Sciences, 2018)
Improving fatigue life is one of the most important issues in mechanical design; an investigation has been conducted on Al 2017-T4. Group of samples have been machined and prepared, some of specimens have been treated using the ultrasonic impact treatment (UIT) with one line peening. The fatigue tests were carried out under constant and variable amplitude (R=-1) at ambient temperature, in order to find out the fatigue life S-N curve and strength after treatment. It has been found significant increasing in strength after it was treated by (UIT). The fatigue strength is improved after treatment up to 4.16% at 107 cycles, enhancement are present with 24% and 18.78% for the cumulative fatigue lives low-high and high–low respectively. These results also show a strong tendency of increasing of fatigue strength after application of (UIT) with increase in mechanical properties of material used.